Near-infrared nanosecond pulsed laser ablation of silver nanowire in aqueous media for low-power and low-debris laser processing. (16th September 2020) - Hwang, June Sik; Park, Jong-Eun; Kim, Gun Woo; Lee, Huseung; Yang, Minyang
Abstract: Silver nanowire (Ag NW) is used as an attractive alternative material to fabricate flexible transparent conductive electrodes (TCE) instead of indium tin oxide, which has brittle characteristics and unstable processing expenses. For practical applications of Ag NW TCE, a proper patterning process is essential because the Ag NW layer is usually formed from the solution process. Laser ablation is one of the promising patterning processes for fabricating Ag NW-based optoelectronic devices. Among the laser processes, the nanosecond near-infrared pulsed laser ablation (NIR PLA) is considered advantageous because it is cheaper than ultrashort or ultraviolet pulsed lasers and causes little damage to the flexible substrate. However, since the Ag NW absorbance in this wavelength is very low, laser processing of Ag NW can deteriorate processing quality due to the remaining debris that resulted from incomplete evaporation of Ag NW. In this study, we report NIR PLA of Ag NW in aqueous media that improved the processing results of Ag NW laser patterning. We found that effective debris removal with a low fluence was a result of advantages such as the reduced heat-affected zone and dispersion of silver nanoparticle debris in the liquid media. Under different processing parameters, the performance of patterned Ag NW improved in liquid media compared to the ambient condition. Significant improvements in the processing quality were also observed in the laser patterning of Ag NW on the flexible substrate without any degradation. Consequently, the patterned flexible Ag NW TCE was successfully fabricated via the proposed process.